Professor Andrzej Duda in memoriam - Penczek, S.; Lewinski, P.; Pretula, J.; Socka, M. (Polimery, 2021)
This paper is describing major scientific achievements of the recently late Professor Andrzej Duda, Chairman of the Department of Polymer Chemistry of The Centre of Molecular and Macromolecular Studies of Polish Academy of Sciences. Professor Duda published over 100 scientific papers and has given several dozens of plenary and invited lectures at the scientific symposia. However, in the present paper, we are mostly describing accomplishment that all of us, and also Professor, have considered as his seminal work, that solved a long time controversial subject. Namely, how to influence reactivities of chiral monomers, using chiral catalysts. Professor Duda had shown, and this subject is mostly described, that reactivity of a chiral monomer can be unchanged (when compared with an achiral catalyst) when polymerized with catalyst of the same chirality and may be many times depressed (the feature highly valuable in several instances) when polymerized with a catalyst with an opposite chirality. This feature is very important in the copolymerization processes, when chiral monomer is much more reactive than the other comonomer. Besides, some other contributions of Professor Duda to Polymer Sciences are also, although briefly mentioned. Full list of papers is given in the second part of the paper.